FAKTOR PENYEBAB PESERTA DIDIK LUPA TERHADAP MATERI PELAJARAN YANG TELAH DIAJARKAN OLEH GURU DI SMA KARTIKA I-5 PADANG - Sari, Mira Seplita (Bimbingan dan Konseling, 2014)
The background of this research because of there are many students forget for the lesson of material that teached by teacher. Then the purpose of this research is to describe the couse of factor the student forget to the lesson of material that teached by teacher. It see from the changes of their attitude and interest, the changes of the environment situation learns of students, pressure on existing subject material, and thy are not use the material that given by teacher. This research is Descriptive Cuantitative research with population all of student in Senior High School Kartika I-5 Padang, it is amount 1118 students. Sampling used Stratified Random Sampling the number 92 students. The instrument used is questionnaire. Data of analisis used percentage formula and determination of the interval using formulation of criterion sturgess. Based on the research result, the factor changes in attitudes and interests serve the cause of forgetting by 2% students. The factor changes of the environment situation learns serve the cause of forgetting by 1,1% students. The factor of the pressure on existing subject material serve the cause of forgetting by 1% students and the factor that student are not used the material lesson serve the cause of forgetting by 5% students.